Analisa Keselamatan dan Kesehatan Kerja Menggunakan Metode HIRARC di PT. Byung Hwa Indonesia - Yasir Arafat; Rianita Puspa Sari (LPPM Politeknik LP3I Medan, 2021)
In the work environment of a company, it cannot be denied that the risk of possible work accidents can occur. The number of work accidents in Indonesia shows an increase every year until 2018 which is the highest accident rate in the last 28 years. Historical data of PT. Byung Hwa Indonesia, which is engaged in manufacturing which produces electronic and automotive components, has recorded a number of work accidents that have occurred up to 2019. The data shows that many work accidents are caused by hazards that are not optimally controlled. Therefore, it is necessary to conduct research on the hazard identification process with a risk assessment which aims to identify the factors that can cause work accidents and provide suggestions for controlling the factors that can cause work accidents. The research was conducted with a qualitative descriptive approach and risk management used in the hazard identification process, namely Hazard Identification, Risk Assessment and Risk Control (HIRARC). From the results of the study it can be concluded that, in the activities carried out by the operator on the injection machine there are 12 factors out of 5 activities that can cause work accidents and on the shootblast machine there are 5 factors from 1 activity that can cause work accidents. The total factors that can cause work accidents are 17 factors and the possibility of a work accident occurring at the low level is 24%, medium 41%, and high 35%. There are several ways to minimize the occurrence of work accidents from these 17 factors, namely by providing Personal Protective Equipment (APD) in the form of glasses, safety shoes, earplugs, gloves and arm protectors. Furthermore, socializing the application of Standard Operational Procedure (SOP) in work and engineering by redesigning the layout of the existing machines on the production floor.